Stacking Analysis of Higher Thinking Skills of Class V Elementary School Students on the Material of Movement Organs Using the RADEC Model - Nur Fauziah; Wati Sukmawati (Postgraduate, University of Mataram, 2023)
The purpose of this research is to use a Rasch model analysis to determine how integrating RADEC (Read, Answer, Discuss, Explain, and Create) learning in schools influences students' ability to think critically about the topic of locomotion. This descriptive research is a quantitative study conducted in early 2023 with a sample size of 29 students. The results of the pretest and the posttest were collected, and the Rasch Stacking Analysis method was used to examine them. The implementation of the RADEC learning paradigm (Read, Answer, Discuss, Explain, and Create) improved the critical thinking skills of students of all ability levels, according to the findings. Reading, Analyzing, Discussing, Explaining, and Creating (RADEC) trains students for independent and group learning. Starting from reading to the last stage, namely making free work through problem-solving activities carried out so that students are trained in high-order thinking skills. Students' high-level thinking skills have improved to the very excellent, good, and enough categories after participating in learning utilizing the RADEC paradigm. The difference between the logit readings before and after the test demonstrates this improvement. Applying the RADEC learning model to students' higher-order thinking skills shows that students experience improvement, as seen from the results of the pretest and posttest, which are processed using the Rasch stacking analysis model. Students are trained in high-order thinking skills students with high level. Â